Perancangan Aplikasi Presensi Berbasis Web untuk Karyawan Magang di PT. Sembilan Pilar Semesta - Tony; Marcel Alexandro Rumbang (Fakultas Teknologi Informasi Universitas Tarumanagara, 2024)
PT Sembilan Pilar Semesta is one of the companies engaged in cybersecurity services. The working system implemented at PT Sembilan Pilar Semesta is shifting. This has caused management to find it difficult to monitor the attendance of employees, especially interns. Moreover, with the manual attendance system for interns using paper to record attendance, it allows for the manipulation of attendance data. Based on the existing issues, the author developed a Web-Based Attendance Application Design for Interns at PT. Sembilan Pilar Semesta to facilitate management in monitoring performance and attendance lists of intern employees. This web-based application design uses the SDLC (Software Development Life Cycle) Waterfall model, with the Laravel framework, and the PHP (Hypertext Preprocessor) programming language along with a MySQL database. In this website-based attendance system, interns can record their attendance. The stored data can be viewed by the admin for data management and monitoring.